2018
DOI: 10.1080/09546634.2018.1476654
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mental health outcomes among adults with psoriasis on biologic versus oral therapies: a population-based study

Abstract: Therapeutic choices for psoriasis impact mental health outcomes. Biologic therapy is associated with reductions in psychological distress and depression as compared to oral therapy in the U.S. adult moderate-to-severe psoriasis population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…There is some evidence that biologic treatment reduces depression in patients with psoriasis, 21,22 which is consistent with the hypothesis that biologics have this additional benefit. The role of the immune system in depression is well established, 23 so it is plausible that anti-inflammatory therapy for the lung reduces depression, but depression is also a correlate of other somatic and psychological symptoms, the etiology of which is linked to the Networks are complex systems of massive simultaneous causal connections.…”
supporting
confidence: 67%
“…There is some evidence that biologic treatment reduces depression in patients with psoriasis, 21,22 which is consistent with the hypothesis that biologics have this additional benefit. The role of the immune system in depression is well established, 23 so it is plausible that anti-inflammatory therapy for the lung reduces depression, but depression is also a correlate of other somatic and psychological symptoms, the etiology of which is linked to the Networks are complex systems of massive simultaneous causal connections.…”
supporting
confidence: 67%
“…Effective biologic psoriasis treatments reduce signs and symptoms of psoriasis, lower disease impact (DLQI) and may also improve mental health outcomes ( 50 , 51 ). Examination of depression through a prospective, longitudinal psoriasis registry (PSOLAR) demonstrated that treatment with biologics in moderate-to-severe psoriasis patients may reduce the risk of depressive symptoms ( 50 ).…”
Section: Depression and Psoriasismentioning
confidence: 99%
“…The beneficial effect was more significant with continuous treatment 24,25 . Biological treatments seem more effective in reducing depression and insomnia than DMARDs 24,26 . However, there is a lack of robust comparative data between the different biological drugs.…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Biological treatments seem more effective in reducing depression and insomnia than DMARDs. 24,26 However, there is a lack of robust comparative data between the different biological drugs. Although adalimumab, etanercept and ustekinumab were associated with a statistically significant reduction in depressive symptoms, comparison between the drugs could not be made due to different rating scales being used.…”
Section: Clinical Recommendationsmentioning
confidence: 99%